TEOLOGI PENGHORMATAN UPAYA MISIOLOGI MELALUI DIALOG KRISTEN DENGAN RITUS MANGONGKAL HOLI DALAM BUDAYA BATAK TOBA - Ruth Anugrah Olivia (Jurnal Matetes STT Ebenhaezer, 2023)
Missiology and the spread of the Christian faith in Indonesia should have specifics, because in the Indonesian context, missiology and the spread of Christianity are directly related to the spread of culture in Indonesia. When working with Batak culture in Sumatra, it is necessary to use culturally sensitive missiology. This article uses a qualitative method with a dialectical approach between the Gospel and culture. The results showed that Batak culture, especially Mangongkal Holi, can be used to carry out missionary movements among the Batak people so that the Gospel can be accepted and explained from a biblical and cultural point of view